Analysis of Fatigue Failure of Francis Turbine Runner at Derbendikhan Hydropower Station - Saeed, Raza Abdulla (Sulaimani Journal for Engineering Sciences, 2017)
Fatigue failures in Francis turbine runner are frequently occurred in hydropower plants, causing unexpected plant downtime and considerable financial loss. Decades of operational experience have shown that turbine runners develop fatigue cracks in areas, where stress concentrations and material defects coincide. In Francis turbine runners, cracks tend to propagate from the transition of the welded T-joint between the blade and the band or crown. This type of turbine runner, which operate under a wide range of heads and outputs, are subjected to considerable dynamic forces which can lead to fatigue cracking. The magnitude of these forces is a function of the hydraulic pressure, the water velocity and the geometry of the stationary parts guiding the water into the runner. This paper presents the water pressure and bending stresses for different operational conditions in a Francis runner of a Derbendikhan hydropower station. At the first step, the dynamic fluid calculation is used to determine the fluctuating water pressure on the blade of the runner. At the second step, for a period of operational nominal bending stress due to the fluctuating water pressure are determined. The result indicates that the hydropower plant was operated with the high fluctuating water pressure which is responsible for inducing bending stress response. The high bending stress on the blade is a probable reason for fatigue failure. Furthermore, the paper discusses the fatigue analysis of the runner. Typical results are presented and discussed.
Keywords: Fatigue Failures; Francis Turbine Runner; Dynamic Fluid Calculation; Nominal Bending Stress